Arborescent Polypeptides for Sustained Drug Delivery. (5th July 2016) - Alsehli, Mosa; Gauthier, Mario
ABSTRACT: Polypeptides are receiving increasing attention as building blocks to create nanostructures for biomedical applications. The first goal of this investigation was to explore the influence of the reaction conditions in the synthesis of well-defined dendritic graft (arborescent) polypeptides from amine-terminated poly(γ-benzyl L-glutamate) (PBG) chains. The optimization was carried out in terms of the reaction temperature, solvent, reaction time, and mole ratio of reactants and coupling agents. Size exclusion chromatography served to evaluate the grafting reaction in terms of grafting yield (fraction of side chains coupled with the substrate) and coupling efficiency (fraction of coupling sites consumed on the substrate). The maximum grafting yield and coupling efficiency achieved were 67% and 74%, respectively. These arborescent PBG substrates were subsequently grafted with poly(ethylene oxide) segments forming a hydrophilic shell, to obtain water-dispersible unimolecular micelles useful as delivery vehicles for doxorubicin.